Fate, residues and dietary risk assessment of the fungicides epoxiconazole and pyraclostrobin in wheat in twelve different regions, China - Zixi Zhao; Runxia Sun; Yue Su; Jiye Hu; Xiaolu Liu (Ecotoxicology and Environmental Safety, 2021)
The fungicides epoxiconazole and pyraclostrobin have been widely used to control wheat fusarium head blight. This study was designed to investigate the dissipation behaviors in different climate regions and provide data for the modification of maximum residue limits of the two fungicides. Wheat samples were collected from field sites in twelve different regions, China and analyzed with an HPLC-MS/MS method for simultaneous detection of epoxiconazole and pyraclostrobin in wheat. The average recoveries of epoxiconazole and pyraclostrobin in wheat matrix were 87–112% and 85–102%, respectively, with the relative standard deviations ≤8.1%. The limits of quantification of epoxiconazole and pyraclostrobin in grain and straw were both 0.01 mg/kg. The dissipations of epoxiconazole and pyraclostrobin followed first-order kinetics, with the half-lives of 10.3 days and 7.6 days, respectively. The terminal residues of epoxiconazole and pyraclostrobin in grain were below 0.034 and 0.028 mg/kg, separately, both lower than the maximum residue limits recommended by China. Based on Chinese dietary pattern and terminal residue distributions, the risk quotients of epoxiconazole and pyraclostrobin were 13.9% and 65.9%, respectively, revealing the evaluated wheat exhibited an acceptably low dietary risk to consumers.